Open adrenalectomy for medium sized adrenocortical tumour: How I do it? - Sameh, Wael M.; Kotb, Ahmed Fouad (Canadian Urological Association Journal, 2015)
Introduction: The aim of our work was to report our experience in managing cases with medium-sized adrenocortical carcinoma by the high retroperitoneal extra pleural approach. Methods: During the past 2 years, 10 patients with suspected adrenocortical carcinoma were managed by our technique: the high supra 10th rib, retroperitoneal extra pleural approach. We included cases with 5 to 10 cm adrenal masses, suspected as adrenocortical carcinoma. Results: The mean patient age was 38 years (range: 26–44), the median tumour volume was 7 cm (range: 5–8). Of the 10 patients, 7 were female. Of the patients, 6 had right- and 4 had left-sided tumours. Intraoperatively, all cases had proper surgical removal, with no apparent residual tumour tissue. No single patient required a chest tube or developed respiratory problems. There were no major vascular injuries during surgery. We did not compare our findings to the standard lateral or subcostal approaches, as in our institution we adopt this high lateral approach for medium-sized tumours, while managing larger tumours with transperitoneal subcostal approach and smaller tumours laparoscopically. Conclusion: The high supra 10th lateral retroperitoneal, extra pleural approach is a safe, doable technique, allowing easy access to medium-sized suprarenal tumours and its vasculature, for cases suspected to be adrenocortical carcinoma.